2017
DOI: 10.1155/2017/8590251
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Property of a Newly Designed Assembly Locking Compression Plate: Three-Dimensional Finite Element Analysis

Abstract: In this study, we developed and validated a refined three-dimensional finite element model of middle femoral comminuted fracture to compare the biomechanical stability after two kinds of plate fixation: a newly designed assembly locking compression plate (NALCP) and a locking compression plate (LCP). CT data of a male volunteer was converted to middle femoral comminuted fracture finite element analysis model. The fracture was fixated by NALCP and LCP. Stress distributions were observed. Under slow walking load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…investigated the functional performance of femur after distal femur fracture and fixation by different types of implants 8. Such comparative studies are still performed today as demonstrated by Zhou et al ., who compared the biomechanical stability and stress of two locking compression plates for middle femoral fracture 49. Many FE studies on proximal humerus plates belong to this category as they investigated the effect of bone cement augmentation, medial support and screw configurations 15,23,44,47…”
Section: Introductionmentioning
confidence: 99%
“…investigated the functional performance of femur after distal femur fracture and fixation by different types of implants 8. Such comparative studies are still performed today as demonstrated by Zhou et al ., who compared the biomechanical stability and stress of two locking compression plates for middle femoral fracture 49. Many FE studies on proximal humerus plates belong to this category as they investigated the effect of bone cement augmentation, medial support and screw configurations 15,23,44,47…”
Section: Introductionmentioning
confidence: 99%
“…Details of this procedure are given by Schileo et al (2007). The femur model was fully constrained distally to satisfy equilibrium according to earlier studies (Behrens et al, 2009;Zhou et al, 2017). The equivalent strain at the element centroid was computed using the linear-elastic solver implemented in Abaqus (Dassault Systems, USA).…”
Section: Muscle and Joint Forces And Femoral Strain During Activitymentioning
confidence: 99%
“…In order to sustain pressurized loads, they must be stiff and able to resist deformation. Metal implants must also be light to facilitate motion [ 40 , 41 , 42 ].…”
Section: Different Applications Of Metal Implants In Clinicmentioning
confidence: 99%